Kajian Tentang Non-Muslim Keturunan Siam di Kelantan - Mohd. Zin, Ab. Aziz (Jurnal Usuluddin, 1998)
This article discusses Siam's community in Kelantan, especially from the point of view of their religion. One of the important findings in this research is that the people of Siam in Kelantan are not quite strong in their religion, although they look like strong. This article also reveals the conduct of Malays which are liked and disliked by the Siameses in Kelantan. The article will be useful to those who want to know about the Siam's community in Kelantan, because it will ease the efforts to unite Malaysian society.